Strategi dan Jenis Kelamin Mengajar Renang Gaya Bebas untuk Siswa Sekolah Dasar - Firmansyah Dlis (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The objective of this research is to investigate learning strategy of frees style swimming for elementary schools’ students related to foot striking amount and sex. The subjects were 30 girls and 30 boys’ first grade elementary schools’ students. The collected data were analyzed by two ways ANOVA and Newman Keluls test. This research found there is interaction between sex and swimming techniques training in the first grade elementary schools’ students.